Biochemical characterization of tirabrutinib and other irreversible inhibitors of Bruton's tyrosine kinase reveals differences in on - and off - target inhibition - Liclican, Albert; Serafini, Loredana; Xing, Weimei; Czerwieniec, Gregg; Steiner, Bart; Wang, Ting; Brendza, Katherine M.; Lutz, Justin D.; Keegan, Kathleen S.; Ray, Adrian S.; Schultz, Brian E.; Sakowicz, Roman; et al. (Biochimica et biophysica acta. General subjects, 2020)
Bruton's tyrosine kinase (BTK) is a key component of the B-cell receptor (BCR) pathway and a clinically validated target for small molecule inhibitors such as ibrutinib in the treatment of B-cell malignancies. Tirabrutinib (GS-4059/ONO-4059) is a selective, once daily, oral BTK inhibitor with clinical activity against many relapsed/refractory B-cell malignancies. Covalent binding of tirabrutinib to BTK Cys-481 was assessed by LC-MSMS analysis of BTK using compound as a variable modification search parameter. Inhibition potency of tirabrutinib, ibrutinib, acalabrutinib, and spebrutinib against BTK and related kinases was studied in a dose-dependent manner either after a fixed incubation time (as used in conventional IC50 studies) or following a time course where inactivation kinetics were measured. Tirabrutinib irreversibly and covalently binds to BTK Cys-481. The inactivation efficiency kinact/Ki was measured and used to calculate selectivity among different kinases for each of the four inhibitors studied. Tirabrutinib showed a kinact/Ki value of 2.4 ± 0.6 × 104 M−1 s−1 for BTK with selectivity against important off-targets. For the BTK inhibitors tested in this study, analysis of the inactivation kinetics yielded a more accurate measurement of potency and selectivity than conventional single-time point inhibition measurements. Subtle but clear differences were identified between clinically tested BTK inhibitors which may translate into differentiated clinical efficacy and safety. This is the first study that offers a detailed side-by-side comparison of four clinically-relevant BTK inhibitors with respect to their inactivation of BTK and related kinases. •The inactivation kinetics of four clinically-relevant BTK inhibitors on BTK and related kinases are characterized.•Kinetics were measured for tirabrutinib, ibrutinib, acalabrutinib, and spebrutinib.•Selectivity between kinases was determined based on the inactivation kinetics.•Tirabrutinib irreversibly and covalently binds to the Cys-481 residue of BTK and is a potent and selective BTK inhibitor.